SOLO-YOGYA INTO 360-DEGREE PHOTOGRAPHY - Jauhari, Jauhari (Seni Media Rekam ISI Surakarta, 2021)
Currently, technological developments have made it possible for photographic works not only to be present in the form of a flat 180 degree two-dimensional panorama, but even being able to present reality with a 360 degree perspective. This research on the creation of photographic works aims to optimize photographic equipment for photographing with a 360 degree perspective. Eventhough there are many 360 degree application in smartphones, but using a DSLR camera to create works with a 360 degree perspective has the advantage that it can be printed in large sizes with high resolution without breaking the pixels. The method of creating this work is based on the experimental process of developing DSLR camera equipment. This 360 degree photography creation technique uses the 'panning-sequence' technique with 'continuous exposure' which allows the images captured by the camera can be combined or mixed into one panoramic image. In addition to getting an important and interesting visual appearance, the presence of a 360 degree perspective in this work can also give a new nuances in the world of the art of photography.